Health policy for the poor: An exploration on the take-up of means-tested health benefits in Turkey - (:unkn) unknown (PERGAMON-ELSEVIER SCIENCE LTD, 2015)
Recent healthcare reform in Turkey aims at achieving universal coverage with the introduction of General Health Insurance (GHI). As part of GHI, the state assumes the provision of health insurance coverage to those unable to afford the public health insurance premiums conditional on a means-testing procedure where the official threshold is set as one-third of the gross minimum wage. This article aims at exploring in Turkey the prevalence of non-take up of means-tested health insurance for the poor and the consequent financial burdens for those poor segments outside the coverage. Based upon Statistics of Income and Living Conditions micro data, the non-take-up rate is estimated to be around 44%, where the prevalence of non-take-up is lower yet still high, i.e. around 30%, for households with very low incomes as well as those with elderly or ill members. The results from a separate health expenditure survey on urban poor, which is specifically designed and implemented by the authors, reveal that poor households without health insurance coverage are faced with significant out-of-pocket expenditures. About 5% of those households without coverage were found to have inpatient expenditures that exceeded 20% of their annual disposable household income. Also, among the households without coverage but with at least one inpatient visit over the last two years, the median expenditure was reported as high as 8% of the annual household income as opposed to 0% median value for those with GHI. The results highlight that a large proportion of poor population still lacks public health insurance despite the overarching aim of universal coverage. (C) 2015 Elsevier Ltd. All rights reserved.
Keywords: Health policy; Access to health; Take-up rate; Turkey; Out-of-pocket expenditures; CARE; COVERAGE